Saturday

April 19, 2014

April 19, 2014

Posted by **Sheryl** on Saturday, October 6, 2012 at 7:34pm.

- Algebra -
**Henry**, Sunday, October 7, 2012 at 8:11pm6(2x+1)/(2x-1)(2x+1)-2(2x-1)/(2x-1)(2x+1).

(12x+6-4x+2)/(2x-1)(2x+1) =

(8x+8)/(2x-1)(2x+1)=

8(x+1)/(2x-1)(2x+1).

**Related Questions**

Rational Expression - (x+1/2x-1 - x-1/2x+1) * (2x-1/x - 2x-1/x^2) (x+1/2x-1 - x-...

Algebra - Need help with this problem, 2x+y=6 solve for y 2x+y=6 subtract 2x ...

college algebra - Passing thru point (1,4); perpendicular to 2x+y=5 How do I ...

TO KIM - can you help me with this |2x - 3|^2 - 6|2x - 3| + 5=0 I know you are ...

math - if (2x-3):(y+4)=k where k is a constant and x=4 when y=2 then find x when...

algebra - This is how my book shows it, but I don't know solve the equation by ...

Algebra - I multiplyed x^2-2x+2 times x^2+2x+2. The book suggested the order ...

math - how many times does the graph of y= 2x squared -2x+3 intersect the x-axis...

Math33333 - Please help me! Problem: x+2 x-3 _________ - _________ 2x^2+5x+2 2x^...

math ALGEBRA - Solve by graping the foll: A. 2X+Y=5 3X-Y=10 B.2X=Y+1 2X-Y=5 I ...